Validation of Self-Reported Smoker and Second Hand Smoke Exposure by Urinary Cotinine within The Malaysian Cohort Project - Noraidatulakma Abdullah; Shariffah Huzaimah Al-Junid; Mee Lee Looi; Siok Fong Chin; Ezanee Azlina Mohd Haniff; Syed Zulkifli Syed Zakaria; Rahman Jamal (Journal of Biomedicine and Translational Research, 2019)
Background: Validation of self-reported questionnaire is very crucial in ensuring the quality and reliability of data collection. Objective: The aim of this study were i) to validate the questionnaire on tobacco smoke intake and second hand smoke exposure among The Malaysian Cohort (TMC) subjects through the determination of urinary cotinine levels, ii) to determine the optimal cut-off point of urine cotinine that discriminates smokers from non-smokers and iii) to estimate misclassification rate between self-reported smoking and urinary cotinine level.Methods: Urine samples from a total of 775 The Malaysian Cohort subjects (104 smokers, 102 former smokers and 569 non-smokers) were obtained and urinary cotinine levels were determined by high-performance liquid chromatography (HPLC). Differences between groups were compared using Kruskal Wallis and Mann-Whitney tests. The Receiver Operating Characteristic (ROC) curved was performed to define the optimal urinary cotinine cut-off point.Results: Urinary cotinine concentration significantly (p<0.001) correlated with smoking status (r=0.46), the average number of cigarettes smoked per day (r=0.53), duration of smoking (r=0.33) and number of cigarettes packed per year (r=0.47). Smokers and second hand smokers have significantly higher median cotinine levels (978.40 and 21.31 respectively) compared to non-smokers (15.52) and non-exposed (13.60) subjects. Cotinine level at cut-off value of 1.51 ng/mg creatinine is able to distinguish smokers and non-smokers with a sensitivity of 84.62% and specificity of 81.97%.Conclusion: The Malaysian Cohort self-reported smoking questionnaire is a reliable tool in assessing the use of tobacco and second hand smoke exposure among the subjects.